The Relationship Between APOC1 Expression And Prognostic Parameters And Survival In Colorectal Cancer - Çeçen, Esra; Çalık, Muhammet; Yıldırım, Sena Özcan (Atatürk Üniversitesi, 2025)
Objective: Colorectal cancer (CRC) is the third most common type of cancer worldwide and the second leading cause of cancer-related deaths. Recent studies have illustraten that apolipoprotein C1 (APOC1) promotes carcinogenesis in certain human cancers. The objective of our study was to determine the association between APOC1 expression and prognostic factors, and survival. Methods: H&E-stained and immunohistochemical(IHC) preparations from colon resection specimens of 90 patients, diagnosed between 2008 and 2018, were examined. APOC1 overexpression was evaluated using an IHC score based on nuclear staining intensity (0-3) and the percentage of positive tumor cells (0-4). Pearson's Chi-Square and Fisher’s exact test were employed to investigate the association between APOC1 expression and prognostic parameters statistically. Kaplan Meier’s and Cox regresion tests were employed to investigate the association between APOC1 expression and survival. Results: The median age of the patients was 63.3 years (Min:34, Max:88). No statistically significant correlation was revealed between APOC1 staining index and gender, age, tumour localisation, histological grade, tumour infiltrating lymphocytes, lymphovascular invasion, perineural invasion, N stage, metastasis and TNM stage (p>0.05). Hıgh IHC expression of APOC1 was correlated with macroscopic tumour diameter and T stage (p

Amaç : : Kolorektal kanserler, dünya genelinde en sık görülen üc?üncü kanser türü olup kansere bağlı ölümlerde ise ikinci sırada yer almaktadırlar. Son dönemlerde Apolipoprotein C1'in (APOC1) bazı insan kanserlerinde karsinogenezi desteklediğini gösteren çalışmalar yapılmıştır. Çalışmamızda KRK’lerde APOC1 ekspresyonunun prognostik faktörler ve sağkalım ile ilişkisini belirlemeyi amac?ladık. Yöntemler : : 2008 ile 2018 yılları arasında tanı konulan 90 hastanın kolon rezeksiyon örneklerinden alınan H&E boyalı ve immünohistokimyasal (IHK) preparatlar incelendi. APOC1 aşırı ekspresyonu, nükleer boyama yoğunluğu (0-3) ve pozitif tümör hücrelerinin yüzdesi (1-3) temel alınarak IHK skoru kullanılarak değerlendirildi. APOC1 ekspresyonu ile prognostik parametreler arasındaki ilişkiyi istatistiksel olarak analiz etmek için Pearson Ki-Kare ve Fisher’s exact testi kullanıldı. APOC1 ekspresyonu ile sağkalım arasındaki ilişkiyi analiz etmek için Kaplan Meier ve Cox regresyon testleri kullanıldı. Bulgular Çalışmada hastaların median yaşı 63,3’tür. KRK’li dokularda yüksek APOC1 ekspresyonu ile olguların makroskopik tümör c?apı ve T evresi arasında anlamlı ilişki tespit edildi (p
Kolorektal Kanserlerde APOC1 Ekspresyonunun Prognostik Parametreler Ve Sağkalım İle İlişkisinin Araştırılması
Keywords: Oncologic Surgery; Cerrahi Onkoloji